Pelatihan Penyusunan Asesmen Projek Penguatan Profil Pelajar Pancasila - Nurfitra Yanto; Ramlawati Ramlawati; Nur Indah Sari; Zulqifli Alqadri (Universitas Negeri Malang, 2024)
Abstract: This activity aims to provide training and assistance in preparing the Assessment for the Strengthening Pancasila Student Profile (P5) Project, especially for science teachers in Bulukumba Regency. P5 assessment is an important part of implementing the independent curriculum in schools. The large number of schools that have just implemented the independent curriculum is the background for the importance of carrying out these activities. The methods applied in this activity are presentation and discussion methods. Evaluation of the implementation of this service is carried out using observation techniques and providing response questionnaires. Training on preparing the Assessment for the Strengthening Pancasila Student Profile (P5) Project in Bulukumba Regency was carried out well and smoothly. The training participants consisted of 63 people from various middle and high schools in Bulukumba Regency. Participants were very enthusiastic in this activity. The preparation of the P5 assessment concentrates on the theme of a sustainable lifestyle. This is because this theme has a direct connection with science material. After this activity, participants were given an evaluation and it was discovered that participants' understanding of the P5 assessment, especially the theme of sustainable lifestyle, was very high. The implementation of the independent curriculum, especially P5, still faces many challenges. This still needs to be paid attention to by the government, schools and other related parties. Abstrak: Kegiatan ini bertujuan untuk memberikan pelatihan dan pendampingan penyusunan Asesmen Projek Penguatan Profil Pelajar Pancasila (P5) khususnya bagi guru-guru IPA di Kabupaten Bulukumba. Asesmen P5 merupakan bagian penting pada pelaksanaan kurikulum merdeka di sekolah. Banyaknya sekolah yang baru menerapkan kurikulum merdeka menjadi latar belakang pentingnya kegiatan dilakukan. Metode yang diterapkan dalam kegiatan ini adalah metode presentasi dan diskusi. Evaluasi pelaksanaan pengabdian ini dilakukan dengan teknik observasi dan pemberian angket respon. Pelatihan penyusunan Asesmen Projek Penguatan Profil Pelajar Pancasila (P5) di Kabupaten Bulukumba terlaksana dengan baik dan lancar. Peserta pelatihan terdiri dari 63 orang dari berbagai sekolah SMP dan SMA di Kabupaten Bulukumba. Peserta sangat antusias dalam kegiatan ini. Penyusunan asesmen P5 berkonsentrasi pada tema gaya hidup berkelanjutan. Hal ini disebabkan karena tema ini beririsan langsung dengan materi IPA. Setelah kegiatan ini, peserta diberikan evaluasi dan diketahui bahwa pemahaman peserta terhadap asesmen P5 khususnya tema gaya hidup berkelanjutan sangat tinggi. Pelaksanaan kurikulum merdeka khususnya P5 masih mendapatkan banyak tantangan. Hal ini masih perlu menjadi perhatian oleh pemerinta, sekolah dan pihak-pihak lain yang terkait.